The Effects of Icariin on Enhancing Motor Recovery Through Attenuating Pro-inflammatory Factors and Oxidative Stress via Mitochondrial Apoptotic Pathway in the Mice Model of Spinal Cord Injury - Li, Haotian; Zhang, Xinran; Zhu, Xu; Qi, Xi; Lin, Kaili; Cheng, Liming (Frontiers in Physiology, 2018)
Spinal cord injury (SCI) is a severe medical problem leading to crucial life change. Icariin (ICA) is a natural flavonoid compound extracted from the Chinese herb Epimedium brevicornum which has neuroprotective effects. But little is known about the relationship between ICA and SCI. We hypothesized ICA may enhance motor recovery through attenuating inflammation, oxidative stress and mitochondrial dysfunction. Mice were randomly assigned to sham, SCI, ICA 20 µmol/kg (low dose) and ICA 50 µmol/kg (high dose) groups. And Behavioral, biochemical, molecular biological, immunofluorescent and histological assays were performed. First, ICA enhanced motor recovery greatly at 14, 28, and 42 d and protected spinal cord tissues especially in the high dose group. Meanwhile, ICA decreased the production of interleukin-1 beta, tumor necrosis factor-alpha and inducible nitric oxide synthase at 24 h and 3 d after SCI. The level of mitochondrial reduced glutathione, superoxide dismutase, adenosine triphosphate (ATP), Na+-K+-ATPase, mitochondrial membrane potential, state III respiration rate and the respiratory control ratio were also significantly increased, while malondialdehyde level and Ca2+ concentration were decreased by ICA. Furthermore, ICA decreased the expression of mitochondrial apoptotic proteins at 3 d after SCI. More importantly, transferase UTP nick end labeling (TUNEL) and Nissl staining implied that ICA at a high dose inhibited the neuronal apoptosis after SCI. Our research indicated that early and continuous treatment of ICA at a high dose significantly enhances motor recovery after SCI through inhibiting pro-inflammatory factors, oxidative stress and neuronal apoptosis via mitochondrial apoptotic pathway.